Effect of parenteral nutrition duration on patterns of growth and body composition in very low‐birth‐weight premature infants. Issue 8 (29th October 2021) - Alja'nini, Zaineh; Merlino‐Barr, Stephanie; Brumfiel, Alexa; McNelis, Kera; Viswanathan, Sreekanth; Collin, Marc; Groh‐Wargo, Sharon
Abstract: Background: Parenteral nutrition (PN) is essential to support premature infants' growth and varies with enteral nutrition (EN) advancement rates. Data on PN duration's impact on premature infants' growth are limited. The aim of this multicenter observational study was to determine the effect of early PN duration on body composition at term corrected gestational age (CGA) in very low‐birth‐weight (VLBW) premature infants. Methods: VLBW infants exposed to PN in the first week of life and exposed to significantly different EN regimens were divided into two groups on the basis of early PN duration. Infants with a birth weight (BW) <1000 g and PN duration <28 days and infants with a BW 1000–1500 g and PN duration <14 days were assigned to the "short‐PN" group. Infants receiving PN for longer durations were assigned to the "long‐PN" group. Body composition was assessed via air displacement plethysmography at term CGA or before discharge. Results: Sixty‐two and 53 infants were assigned to the short‐PN and long‐PN groups, respectively. The two groups were significantly different in BW and GA, so a nested case‐control study was conducted after matching 36 infant pairs. Infants in the long‐PN group had significantly lower fat‐free mass (FFM) z ‐scores, but both groups had comparable fat mass (FM) z ‐scores. Long PN was a significant negative predictor of FFM z ‐score in the multivariate regression analysis. Conclusion: In VLBW premature infants, PN duration is negatively associated with FFM z ‐scores at term CGA without affecting FM z ‐scores.